Liderazgo del profesor: objetivo básico de la gestión educativa - Bernal Martínez de Soria, Aurora; Ibarrola García, Sara (Revista Iberoamericana de educación, 2015)
Numerous reports show the relationship between the management, the processes of educational leadership and achievements in the quality of education. In this study we emphasize the importance of teacher’s leadership as a key objective of management in schools who want to distinguish by their pedagogical leadership. We also reviewed the most representative bibliography of the last decade about leadership and education, looking for those publications that refer to teacher’s leadership. We start by defining the concept and weed out the main features of the recent research about the teacher himself as a leader, and highlight the research focus that have been opened recently on the subject. Since the main difficulty is finding sources working this specific issue, we address the issue through existing studies on two topics related: some types of leadership and professional development of teachers.